CARDIOGENIC INSULTS - A. V. Fonyakin (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2009)
Based on the current data available in the literature and the results of his studies, the author characterizes the implication of cardiac diseases in the pathogenesis of cardioembolic and hemodynamic insults. Cardiogenic insults are demonstrated to account for as high as 40% of all the causes of ischemic insult. The leading causes of cardioembolic stroke are considered to be nonrheumatic atrial fibrillation, postinfarct changes, and rheumatic heart disease. The pathogenesis of hemodynamic insult (HDI) may be also caused by cardiac pathology that can singly affect blood pressure levels via cardiac output variations. Silent myocardial ischemia, atrial fibrillation, and sick sinus syndrome are regarded as the most common cardiogenic causes of HDI. The importance of a target cardiological study of patients with ischemic insult is accentuated for the effective secondary prevention of cardiogenic insults.